Konsep Supervisi Supervisi Klinis Di Era Smart Society 5.0 - Fil Khiyam, Yunita Maqshurotun; Natania, Friska Oliva (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
Improving the quality of learning can improve student achievement as well. This is influenced by the teacher's teaching behavior to create a conducive learning atmosphere so that learning can run effectively. The role of the teacher is very important in designing a good lesson plan in preparing teaching materials. Modifying teaching patterns is sometimes difficult for teachers who lack this ability, so the role of this clinical supervision activity is as a place of guidance to assist the development of teacher professionalism in teaching. The process of clinical supervision is carried out face-to-face between supervisors and teachers. The supervision process is basically centered on the analysis of discussing matters relating to the teaching and learning process, the analysis is carried out based on evidence of observations that occur in the classroom. Clinical supervision is carried out based on complaints or problems from the teacher which are conveyed to the supervisor. The more often supervision activities are carried out, the more motivation the teacher can develop in developing his teaching skills. Therefore, the principle of clinical supervision is centered on efforts to meet teacher needs so that there must be collaboration and openness between supervisors and teachers in conveying ideas. The purpose of supervision is to find out the teacher's ability to teach while observing developments. Supervisors can make observations of teachers while teaching in class, then hold meetings to discuss feedback and alternative solutions to problems found, then analyze after the meeting as well as formulate solutions that can overcome teacher difficulties in teaching.